2016
DOI: 10.1155/2016/8306071
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Electroconvulsive Therapy in Bipolar Disorder with Mixed Features

Abstract: Introduction. Mixed states represent a frequent presentation of bipolar disorder, associated with higher resistance to psychopharmacology. Limited evidence supports the use of ECT in these patients. We aim to report our experience on treating bipolar mixed states with ECT. Methods. Retrospective data were collected from all bipolar patients submitted to acute ECT treatment, between June 2006 and June 2011. Three groups were created in terms of affective polarity of the episode. CGI rating was used to establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…has support from several uncontrolled trials in mixed episodes. [113][114][115][116][117] As with other mixed presentations, this strategy is recommended for those who have not responded to recommended second-and third-line pharmacotherapy options.…”
Section: Presentationmentioning
confidence: 99%
“…has support from several uncontrolled trials in mixed episodes. [113][114][115][116][117] As with other mixed presentations, this strategy is recommended for those who have not responded to recommended second-and third-line pharmacotherapy options.…”
Section: Presentationmentioning
confidence: 99%
“…Due to the efficacy of ECT in the treatment of manic and depressive episodes, its recent use has extended to bipolar disorder mixed states. This condition has been proven to be extremely difficult to treat, with reports of many patients not responding to pharmacological treatment based on the antipsychotics and mood stabilizers used [167,168]. Retrospective studies have shown a response in patients with mixed states treated with unilateral [169] and bilateral [170] ECT.…”
Section: Bipolar Disordermentioning
confidence: 99%
“…These facts allude to the pernicious nature of mixed symptoms, so that the treating physician must be alert to their presence and be prepared to institute therapeutic strategies which are effective, well tolerated, and have a good safety profile. 8 Fig. 2 provides a pictorial outline of the burden imposed by mixed affective symptoms on the illness course in bipolar disorder, with a depiction of the long term adverse consequences.…”
Section: Mixed Symptoms In Bipolar Disordermentioning
confidence: 99%